A Primary Hydatid Cyst of Thigh Mimicking as Soft Tissue Tumour: Diagnostic Dilemma - Sherkar, Dr Nitin; Mehra, Dr. Bhupendra Mehra; Dubhashi, Dr. Siddharth P.; K, Dr. Senthilkumaran K.; Pusdekar, Dr. Vinod Pusdekar; Fulmali, Dr. Ateet Fulmali (International Journal of Innovative Research in Medical Science, 2024)
Hydatid disease is one of the most prevalent parasitic infections caused by Echinococcus granulosus. It is likely to affect all organs. However, primary hydatid cysts of muscle tissue are so uncommon. A timely and precise diagnosis is critical to avoiding an unnecessary biopsy. Here, we present a case of a 29-year-old female presented with soft tissue swelling over the anterior aspect of the right thigh. The diagnosis of a hydatid cyst was made based on ultrasonography (USG) and magnetic resonance imaging (MRI). A complete surgical excision of the cyst was done with an uneventful postoperative course.